PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PATRIA MARITIM PERKASA - Marici, Angelia; Pandapotan, Rikson (LPPM Universitas Putera Batam, 2019)
The current industrial world has entered associate era of economic process. Development and advancement of technology moreover as intense competition can encourage entrepreneurs to further improve the standard of the merchandise offered so as to vie. The shipping trade in state is essentially situated in Batam, Batam thanks to this condition as a strategic region in finance, particularly within the field of offshore and marine. the aim of this study was to work out the result of activity health and safety on worker performance at PT Patria Maritim Perkasa each part and at the same time. activity health and safety have an effect on worker performance because the variable quantity. The samples used are worker as several as 133 respondents. The sampling assortment technique uses a likelihood sampling and an information announcement technique employing a form (questionnaire). this sort of analysis is quantitative research. chemical analysis includes tests of validity, responsibleness, classical assumption check, multiple linear analysis of constant of determination (R2), f check and t test. the info of this study were processed mistreatment SPSS version twenty five computer code.